Meningitis Due to Haemophilus influenzae Serotype A and Adenovirus: A Rare Case of Co-Infection in a Six-Month-Old Infant - Mazeda, Inês (2025)
Haemophilus influenzae serotype A is a rare cause of meningitis and invasive disease in pediatric patients. A six-month-old infant presented to the emergency room with fever, cough and nasal drip. On admission, the infant was alert and hemodynamically stable but progressively became more lethargic with bulging of the fontanelle. The blood tests revealed a normal leukocyte count and elevated C-reactive protein. Cytology and biochemistry of the cerebrospinal fluid were consistent with bacterial meningitis and treatment with ceftriaxone was initiated. Both blood and cerebrospinal fluid cultures were positive for Haemophilus influenzae. Serotyping of the strain identified Haemophilus influenzae serotype A. Viral detection in cerebrospinal fluid and nasopharyngeal aspirate tested positive for adenovirus. The infant completed 10 days of antibiotic therapy and was fully recovered upon discharge. Although cases of Haemophilus influenzae serotype a meningitis are rare, invasive disease caused by non-B serotypes as well as non-encapsulated isolates have been increasing, emphasizing the need for monitoring and continuous epidemiological surveillance.